1986
DOI: 10.1111/j.1476-5381.1986.tb09494.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive inotropic action of saponins on isolated atrial and papillary muscles from the guinea‐pig

Abstract: The effects of several saponins of animal and plant origin on the contractile activity of atrial and papillary muscles of the guinea‐pig were tested. In a concentration of 1 × 10−5 M, holothurin‐A (HL‐A), holothurin‐B, echinoside‐A, echinoside‐B and sakuraso‐saponin (Saku) exhibited positive inotropic and chronotropic actions whereas desacyl‐jego‐saponin and ginsenoside‐Rd did not. Saponins having a positive inotropic action caused haemolysis of rabbit erythrocytes whereas those without inotropic action did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…Membrane fluidity controls the enzyme activity of biological membranes and has an important role in ion transport (Ma & Xiao, 1998) and the ability of saponins to affect this parameter may explain their effects on cellular function. The inotropic action of saponins, supposed to be caused by their effect on membrane Ca 2+ channels, also did not have any simple correlation with membrane permeability effect (Enomoto et al 1986). Saponins such as ophiopogonins and ginsenocides haemagglutinated human, rabbit, and sheep erythrocytes but were not haemolytic (Takechi & Tanaka, 1995a).…”
Section: Effects On Cell Membranesmentioning
confidence: 99%
“…Membrane fluidity controls the enzyme activity of biological membranes and has an important role in ion transport (Ma & Xiao, 1998) and the ability of saponins to affect this parameter may explain their effects on cellular function. The inotropic action of saponins, supposed to be caused by their effect on membrane Ca 2+ channels, also did not have any simple correlation with membrane permeability effect (Enomoto et al 1986). Saponins such as ophiopogonins and ginsenocides haemagglutinated human, rabbit, and sheep erythrocytes but were not haemolytic (Takechi & Tanaka, 1995a).…”
Section: Effects On Cell Membranesmentioning
confidence: 99%
“…Enomoto et al (1986) studied the positive inotropic effect of saponins of Panax species and concluded that modification of calcium channel might be involved in this effect. 68 Saponins with positive inotropic effect were showed haemolysis in rabbit erythrocytes. A cardioactive steroidal saponin containing rare neogetogenin as aglycon named cistocardin from Ayurvedic medicinal plant Tribulus cistoides (thistle of the hot country) exhibited strong positive inotropic effect at 10 −6 M to 10 −5 M concentration in papillary muscles of Guinea pigs.…”
Section: Cardioprotective Activity Of Saponinsmentioning
confidence: 99%
“…Sea cucumber has been a traditional healthy food for thousands of years. Triterpene glycosides are the most important secondary metabolites of sea cucumbers because of their biological activities, including antifungal, cytotoxic, hemolytic, cytostatic, and immunomodulatory effects [1][2][3][4]. More than 100 of these compounds have been isolated from sea cucumbers.…”
Section: Introductionmentioning
confidence: 99%